2021
DOI: 10.48133/igdirsbd.1008467
|View full text |Cite
|
Sign up to set email alerts
|

Sporcularin Psi̇koloji̇k Beceri̇ Düzeyleri̇ni̇n İncelenmesi̇

Abstract: Bu çalışmanın amacı; sporcuların psikolojik becerilerinin farklı değişkenlere göre incelenmesidir. Araştırmanın evrenini 2020-2021 yılında İstanbulda farklı kulüplerde futbol, voleybol, tenis, yüzme ve atletizm branşlarıyla ilgilenen sporcular oluşturmaktadır. Örneklemini, Avcılar, Beylikdüzü ve Bakırköy'de çeşitli külüplerde en az 3 yıl spor geçmişine sahip 218'kadın ve 210'erkek toplamda 428 sporcudan meydana gelmektedir. Araştırmada "Kişisel Bilgi Formu" ve Erhan ve ark. ( 2015) tarafından Türkçe geçerlik v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
2
0
3
Order By: Relevance
“…When the interaction between psychological skills and gender is examined within the scope of the literature, according to the results of a study conducted by Yıldız and Erhan (78) on athletes engaged in winter sports, no difference was found in the psychological skills of athletes according to gender. This result supports Turkish Journal of Sport and Exercise /Türk Spor ve Egzersiz Dergisi 2023 25(2):289-302 our research, but contrary to this result, in a study conducted by Şahinler (68) on athletes, it was determined that female athletes had higher scores than male athletes regarding their psychological skills.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 77%
See 1 more Smart Citation
“…When the interaction between psychological skills and gender is examined within the scope of the literature, according to the results of a study conducted by Yıldız and Erhan (78) on athletes engaged in winter sports, no difference was found in the psychological skills of athletes according to gender. This result supports Turkish Journal of Sport and Exercise /Türk Spor ve Egzersiz Dergisi 2023 25(2):289-302 our research, but contrary to this result, in a study conducted by Şahinler (68) on athletes, it was determined that female athletes had higher scores than male athletes regarding their psychological skills.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 77%
“…This result supports the research as it reflects the same result as this study. When the literature is examined in terms of the type of sports performed with psychological skills, contrary to the results of the study, it has been revealed as a result of the studies that there are significant differences between individual and team sports in previous studies (68,78). In order for the results to have a wider scope, it is recommended to conduct extensive research on athletes with different demographic characteristics.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 73%
“…Spor psikolojisi alanında en ilgi çekici konulardan biri, spor performansının sağlanmasında önemli rol oynayan zihinsel hazırlık ve buna göre uygulanan psikolojik beceri kriterleridir (Şahinler, 2021). Günümüzde spor psikolojisi uygun ve etkili psikolojik becerilere yönelik antrenmanların geliştirilmesini ve uygulanmasını kapsayan disiplinler arası bir alan, bir bilim dalı olarak kabul görmektedir (Şahinler, 2021;Koruç, 1998). Aynı zamanda spor psikolojisi bir meslek olup, kuramsal olduğu kadar, uygulamalıdır (İkizler, 1997).…”
Section: Introductionunclassified
“…Bu faktörlerden hedef belirleme, imgeleme, kendi kendine konuşma, motivasyonel konuşma, zihnin yönünü değiştirme, kendi kendine eğitim ve aşamalı gevşeme teknikleri, korku ve endişe gibi unsurlarla birlikte bu unsurların zihinde canlanmasında yer alır (Karagenç, 2021;Erhan, Bedir, Güler ve Ağduman, 2015). Tüm bu unsurlar her sporcunun psikolojik performansını ve becerilerini bir sonraki seviyeye taşıması için rehberlik eder (Şahinler, 2021;Konter ,1998;Erdoğan, Zekioğlu, Dorak, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation